Uncertainty parameters of battery energy storage integrated grid and their modeling approaches: A review and future research directions - Reza M.S.; Hannan M.A.; Ker P.J.; Mansor M.; Lipu M.S.H.; Hossain M.J.; Mahlia T.M.I. (Elsevier Ltd, 2024)
The continuously growing population and urban growth rates are responsible for the sharp rise in energy consumption, which leads to increased CO2 emissions and demand-supply imbalances. The power sector is switching to alternative energy sources, including renewable energy resources (RES) such as Photovoltaic (PV) and wind power (WP) and battery energy storage systems (BESS), among others, due to an increase in the use of fossil fuels and their shortage. Since the power generation of these resources is uncertain due to climatic fluctuations and the direct integration of these resources into the power grid is very complex due to the issues such as